Analisis Penerapan Akuntansi Biaya Lingkungan Untuk Keberlanjutan Usaha pada Industri Tahu di Kecamatan Masbagik Kabupaten Lombok Timur - Pratiwi, Widiya; Utami, Luh (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the implementation of environmental cost accounting in the tofu industry in Masbagik District, East Lombok Regency. The research employs a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. The findings indicate that the implementation of environmental cost accounting is still at an early stage, as evidenced by the absence of specific separation and recording of environmental costs. Costs related to liquid waste management, water usage, and production smoke control remain merged within general operational expenses. Specific findings show that although the recording is not yet systematic, business owners already demonstrate a good level of environmental awareness, such as utilizing tofu waste as livestock feed and constructing simple liquid waste channels. Practically, this study provides a foundation for developing a simple MSME-based environmental cost recording model and formulating policies for assistance and the provision of communal waste management facilities. Theoretically, this research reinforces the relevance of environmental cost classification and the triple bottom line concepts in the context of small-scale food industries.